Comparative Analysis of Chinese and Indonesian Vowel Systems - Haryono Candra; Yusup Gumilar Sukma (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
In Chinese and Indonesian languages, a syllable is composed of consonants and vowels. Many researchers have focused on studying consonants and paid less attention to vowels. However, vowels play an essential role in a syllable, which is in fact the most pronounced part of a syllable. It is because of vowels that people can perceive language and communicate with each other. This article takes the Chinese and Indonesian vowels as the research object and makes a comparative analysis of the Chinese and Indonesian vowel systems to reveal the similarities and differences between the two at the level of monophthongs, compound vowels, and allophones. Hopefully, it can make contributions to the development of the Chinese-Indonesian comparative phonology discipline. This paper mainly adopts qualitative research method, that is, combining literature integration method, description method, contrast method and analysis method. It reaches several conclusions: First, the Chinese monophthongs, compound vowels, and allophones are more developed than those of Indonesian; Second, there is contrast between rounded and unrounded lip sounds in the Chinese monophthong system, which does not exist in the Indonesian system; Third, there exists some cases in Chinese compound vowels system that the spelling is inconsistent with the actual pronunciation, but this is not the case in Indonesian. Fourth, Chinese vowels’ allophones are mainly caused by the different positions of vowel in the syllables, while in Indonesian they are mainly affected by the different natures of the syllables. The results of this research can provide some insights for other Chinese and Indonesian language researchers.